Escola Técnica de Goiânia: a institucionalização do ensino médio profissional em Goiás de 1942 – 1950 - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The object of this research is the analysis of the Technical School of Goiânia, as a professional high school institution in the city of Goiânia from 1942-1950. The problem that guides the work is: What are the political and social dynamics that guided the process of institutionalization and that of professional high school in Goiás at the Technical School of Goiânia between 1942 and 1959? The study of the Educational Institution to understand the aspects that made up the institutionalization process of the newly created capital of Goiás is the field of studies that guides the analysis of the object through its political and social organization. The History of Educational Institutions supports the collection and analysis of documentation, from various supports, in order to understand what was the Technical School of Goiânia in the studied period. Organized under the technical education legislation proposed by the Capanema education reforms, the institution had an effective participation in the formation of specialized labor at the secondary level. This research is relevant from the point of view of the reconstruction of an important historical period of the Technical School of Goiânia in its institutional, social, political and, above all, educational aspects.
Tecnhical School of Goiânia: the institutionalization professional high school in Goiás from 1942-1950
Keywords: História da educação; Instituições educativas; Escola técnica de Goiânia; History of education; Educational institutions; Goiânia technical school; CIENCIAS HUMANAS::EDUCACAO